2018
DOI: 10.3390/ijerph15122867
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of ICT Self-Efficacy Scale: Exploring the Relationship with Cyberbullying and Victimization

Abstract: The purpose of this study was to develop and validate the ICT Self-Efficacy Scale and the association of cyberbullying and victimization with ICT self-efficacy. Sample 1 (436 university students) was used to identify the factor structure of the Scale, and sample 2 (1115 university students) provided the data to confirm the factor structure (CFA), and to compute the internal consistency reliability, and convergent validity of the scale. Findings demonstrate that the new scale is a reliable and valid domain-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
1
12
0
2
Order By: Relevance
“…Regarding cyber victimization, findings are in agreement with Mishna et al (2012), who suggested that cyber victims were not aware of the skills related to online safety. Findings for the role of ICT in the involvement of cyberbullying perpetration seems to be consistent with other research which found the positive association between ICT self-efficacy and perpetration of cyberbullying (Xiao and Wong, 2013; Musharraf et al, 2018), and those who reported significant association of cyberbullying perpetration with computer skills (Walrave and Heirman, 2011), and online expertise (Livingstone et al, 2011). A possible explanation for these results may be that those who choose to cyberbully others need skills and ICT self-efficacy may failitate enacting their aggression.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding cyber victimization, findings are in agreement with Mishna et al (2012), who suggested that cyber victims were not aware of the skills related to online safety. Findings for the role of ICT in the involvement of cyberbullying perpetration seems to be consistent with other research which found the positive association between ICT self-efficacy and perpetration of cyberbullying (Xiao and Wong, 2013; Musharraf et al, 2018), and those who reported significant association of cyberbullying perpetration with computer skills (Walrave and Heirman, 2011), and online expertise (Livingstone et al, 2011). A possible explanation for these results may be that those who choose to cyberbully others need skills and ICT self-efficacy may failitate enacting their aggression.…”
Section: Discussionsupporting
confidence: 89%
“…The scale was developed and validated on university students and has good internal consistency with alphas ranging from 0.92 to 0.93 (Musharraf et al, 2018) and alpha 0.92 was found for the present study.…”
Section: Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…Perkembangan ini tentu memberikan kemudahan bagi setiap remaja untuk mendapatkan informasi mengenai semua hal sehingga terkadang tidak dikontrol dan melebihi batas yang seharusnya (Barus, 2019) Korban cyberbullying mendapatkan beberapa macam perilaku diantaranya; korban mendapatkan kata-kata kasar dari pelaku, diancam, menyebarkan rumor hingga merusak pertemanan, membuka akun media sosial korban secara paksa, membagikan gambar tentang korban yang bertujuan untuk mempermalukan korban, mengucilkan korban dari media sosial hingga merekam korban ketika ia dipukuli oleh orang lain dan membagikannya di internet (Lohbeck & Petermann dalam Willard, 2018). Dalam penelitian yang dilakukan oleh (Shemesh &Heiman dalam Musharraf, 2018) individu yang mengalami cyberbullying mempunyai self-efficacy yang rendah dibandingkan orang-orang yang tidak mendapatkan cyberbullying di internet.…”
Section: Pendahuluan Latar Belakangunclassified